The Development Learning Activities on Concentration by using Polya’s Problem Solving Process with Multimedia for Mathayomsuksa 4 students Phadungnaree School - Jansrahang, Sudarat; Soikudrua, Nattharuja; Khechornphak, Thanyaluck; Rundon, Butsayamat; Somtaw, Thanawat (Journal for Developing the Social and Community, 2023)
The objectives of this research were to 1) The development learning activities on concentration by using Polya’s problem solving process with multimedia for mathayomsuksa 4 students in the order to efficiency according to 75/75criteria, 2) Study the index of effectiveness of students who received learning activities by using Polya’s problem solving process with multimedia and 3) Study the satisfaction of students. toward learning activities by using Polya’s problem solving process with multimedia. The sample were 41 persons, mathayomsuksa 4 students, Phadungnaree School. They were selected by Cluster random sampling technique. Research is an Action Research. The research instruments were lesson plans, a learning package, 30 items of four - multiple-choice achievement test and 12 items of questionnaire. Statistics used in data analysis were mean, standard deviation and percentage. analysis were mean, standard deviation and percentage. Results of the research In regard to the efficiency, the research finding indicated that the concentration by using Polya’s problem solving process with multimedia for mathayomsuksa 4 students, in the order to efficiency according to 75/75 criteria (E1/E2 = 79.34/75.53). The index of effectiveness of students who received learning activities by using Polya’s problem solving process with multimedia were equal to 0.6746, Shows that students have progress in learning, increasing the percentage 67.46 The satisfaction of students. toward learning activities on concentration by using Polya’s problem solving process with multimedia was the most (X̅ = 4.85, S.D. = 0.32)